Immunomodulating Therapies in Acute Myocarditis and Recurrent/Acute Pericarditis - Ammirati, Enrico; Bizzi, Emanuele; Veronese, Giacomo; Groh, Matthieu; Van de Heyning, Caroline M.; Lehtonen, Jukka; Pineton de Chambrun, Marc; Cereda, Alberto; Picchi, Chiara; Trotta, Lucia; Moslehi, Javid J.; Brucato, Antonio (Frontiers in Medicine, 2022)
The field of inflammatory disease of the heart or “cardio-immunology” is rapidly evolving due to a wider use of noninvasive diagnostic tools able to detect and monitor myocardial inflammation. In acute myocarditis, recent data on the use of immunomodulating therapies have been reported both in the setting of systemic autoimmune disorders and in the setting of isolated forms, especially in patients with specific histology (e.g. eosinophilic) or an arrhythmic burden. A role for immunosuppressive therapies has been also shown in severe cases of COVID-19, a condition that can be associated with cardiac injury and acute myocarditis. Furthermore, ongoing clinical trials are assessing the role of high dosage methylprednisolone in the context of acute myocarditis complicated by heart failure or fulminant presentation or the role of anakinra to treat patients with acute myocarditis excluding patients with hemodynamically unstable conditions. In addition, the explosion of immune-mediated therapies in oncology has introduced new pathophysiological entities, such as immune-checkpoint inhibitor-associated myocarditis and new basic research models to understand the interaction between the cardiac and immune systems. Here we provide a broad overview of evolving areas in cardio-immunology. We summarize the use of new imaging tools in combination with endomyocardial biopsy and laboratory parameters such as high sensitivity troponin to monitor the response to immunomodulating therapies based on recent evidence and clinical experience. Concerning pericarditis, the normal composition of pericardial fluid has been recently elucidated, allowing to assess the actual presence of inflammation; indeed, normal pericardial fluid is rich in nucleated cells, protein, albumin, LDH, at levels consistent with inflammatory exudates in other biological fluids. Importantly, recent findings showed how innate immunity plays a pivotal role in the pathogenesis of recurrent pericarditis with raised C-reactive protein, with inflammasome and IL-1 overproduction as drivers for systemic inflammatory response. In the era of tailored medicine, anti-IL-1 agents such as anakinra and rilonacept have been demonstrated highly effective in patients with recurrent pericarditis associated with an inflammatory phenotype.